KEGUNAAN GAME DALAM PENGENALAN SEJARAH - Shobri, Taufik; Akbar Hashemi R, Wildan; Anwar, Syaiful (CV. Lafadz Jaya, 2024)
Educational games have become an innovative method in history education that can enhance students' interest and understanding. This research aims to explore how educational games can introduce history in an engaging and effective way. Using a system analysis approach and black box testing, the researchers developed a history-based educational game that is engaging and interactive. The results show that this game provides high overall scores in design and gameplay duration, offering a fun learning experience for users. With proper time management, this educational game can serve as an effective alternative in history education without causing boredom.